The Association Between Knowledge and Practice of Body Mechanic Technique Among Nurses in Emergency Department from Hospital in North Borneo - Nazrin Ahmad; Ting, Shau Chen; Mazlinda Musa; Hamidah Hassan; Syed Sharizman Syed Abdul Rahim; Soong, Shui Fun; Siti Fatimah Saad; Rohani Mamat (International Journal of Medical and Exercise Science, 2021)
Introduction: Body Mechanic Technique (BMT) is a method of moving throughout daily activities, and good body mechanics can help you avoid injury and lower back pain. The aim of this study is to identify the level of knowledge and level of practice among nurses in Emergency Department, Hospital in North Borneo, Sabah regarding Body Mechanic Technique and their relationship. Method: A descriptive cross-sectional study was conducted on 40 staff nurses from Emergency Department, Hospital in North Borneo. Data was collected using validated questionnaire with 15 minutes to timeframe to answer all questions. Data then was analysed using descriptive statistics and Pearson Correlation Coefficient, aided with IBM’s Statistical Package for the Social Science (SPSS) Version 25 statistic software. Result: From this study, it is revealed that majority of the respondents had fair level of knowledge (77.5%) and majority of respondents had good level of practice (55%) regarding BMT. The study also revealed that there is weak correlation between level of knowledge and level of practice regarding BWT, as the Pearson Correlation Test indicates that p value is 0.128. Conclusion: Overall, the level of knowledge and practice regarding BMT among in nurses in ED Hospital in North Borneo are generally fair and there still opportunity for improvement to prevent occurrence low back pain and its complication in the future.